Froggy bakes a cake - London, Jonathan, 1947-; Remkiewicz, Frank (New York : Grosset & Dunlap, 2001)
As he helps his father prepare to celebrate his mother's birthday, Froggy makes a big mess trying to do things his own way.
G1
Keywords: Frogs -- Fiction; Baking -- Fiction; Birthdays -- Fiction; Fathers and sons -- Fiction